Eficácia antimicrobiana de diferentes substâncias químicas auxiliares associadas a diferentes técnicas de preparo do canal radicular - Soligo, Larissa Taís (2017)
The ain objective of this study is to evaluate microbial reduction using different chemical auxiliary chemicals associated with different root canal techniques. A pilot study was carried out to evaluate the antimicrobial activity of Grape Seed Extract (GSE) in the concentrations of 10%, 30% and 50%, Sodium Hypochlorite (NaOCl) 6%, and Calcium Hypochlorite (Ca(ClO)2) 2.5% and 6% by the technique of antibiogram disks by means of direct contact in agar to determine the concentration of GSE to be used in the next study. All concentrations of GSE resulted in the lowest inhibition halos among the active substances. Therefore, GSE 50% was used, because it presented better effectiveness between tested concentrations. After that, 88 standard molar roots were obtained 15 mm in length. E. faecalis (ATCC 19433) was prepared in BHI broth and 100 μl of the culture was introduced into the roots, repeating the procedure every 48 hours for renewal of the culture medium for 21 days. The roots were randomly divided in to 8 groups (n = 11) according to the auxiliary chemical used: NaOCl 6%, Ca(ClO) 2 6%, GSE 50%, and Physiological Serum 0.9% (control group). For each substance two preparation techniques were used: ProTaper Next X1 and X2 and Reciproc R25. The evaluation of the disinfection of different systems and substances was performed by counting CFUs before and after treatments. Statistical analysis was performed using the ANOVA test 22 followed by Tukey's complementary test (α = 0.05). The results showed no statistically significant difference between the active substances (p> 0.05), which were higher than the control group (p <0.05). Statistical similarity was also observed among the preparation techniques (p> 0.05). According to the results, it can be concluded that Ca(ClO)2 6% and GSE 50% present antimicrobial capacity similar to NaOCl, as the technique using Protaper Next was similar to the technique with Reciproc.